Factors Affecting the Thickness of Thermal Aureoles - Annen, Catherine (Frontiers in Earth Science, 2017)
Intrusions of magma induce thermal aureoles in the country rock. Analytical solutions predict that the thickness of an aureole is proportional to the thickness of the intrusion. However, in the field, thermal aureoles are often significantly thinner or wider than predicted by simple thermal models. Numerical models show that thermal aureoles are wider if the heat transfer in the magma is faster than in the country rock due to contrasts in thermal diffusivities or to the effect of magma convection. Large thermal aureoles can also be caused by repeated injection close to the contact. Aureoles are thin when heat transfer in the country rock is faster than heat transfer within the magma or in case of incrementally, slowly emplaced magma. Absorption of latent heat due to metamorphic reactions or water volatilization also affects thermal aureoles but to a lesser extent. The way these parameters affect the thickness of a thermal aureole depends on the isotherm under consideration, hence on which metamorphic phase is used to draw the limit of the aureole.